2010
DOI: 10.1093/gerona/glq108
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Scavenger Receptor–Mediated Endocytosis in Rat Liver Sinusoidal Endothelial Cells

Abstract: Liver sinusoidal endothelial cells (LSECs) play an essential role in systemic waste clearance by effective endocytosis of blood-borne waste macromolecules. We aimed to study LSECs' scavenger function during aging, and whether age-related morphological changes (eg, defenestration) affect this function, in F344/BN F1 rats. Endocytosis of the scavenger receptor ligand formaldehyde-treated serum albumin was significantly reduced in LSECs from old rats. Ligand degradation, LSEC protein expression of the major scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 52 publications
4
46
0
Order By: Relevance
“…Importantly, one of the markers for SECs in zebrafish embryos and adult mammals, Stabilin-2, has been identified as the main HA clearance receptor in the mouse liver. 40 In vitro, Stabilin-2 and its paralog Stabilin - 1 have been shown to bind to a large variety of endogenous (mostly anionic) macromolecules 41 as well as phosphothiorate-modified antisense oligonucleotides (PS-ASO), 42 apoptotic cell bodies, 43 biotinylated albumin, 44 and carbon nanotubes. 45 In vivo , Stabilin-1 and Stabilin-2 were shown to mediate sequestration (but not uptake) by LSECs of aged erythrocytes in a phosphatidylserine-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, one of the markers for SECs in zebrafish embryos and adult mammals, Stabilin-2, has been identified as the main HA clearance receptor in the mouse liver. 40 In vitro, Stabilin-2 and its paralog Stabilin - 1 have been shown to bind to a large variety of endogenous (mostly anionic) macromolecules 41 as well as phosphothiorate-modified antisense oligonucleotides (PS-ASO), 42 apoptotic cell bodies, 43 biotinylated albumin, 44 and carbon nanotubes. 45 In vivo , Stabilin-1 and Stabilin-2 were shown to mediate sequestration (but not uptake) by LSECs of aged erythrocytes in a phosphatidylserine-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Animal models have suggested a loss of the liver's regenerative capacity, as well as impaired liver function with increased age. [14][15][16][17] In a study of 775 patients, Balzan et al reported age over 65 years as an independent predictor of death in multivariate analysis. 18 In a subsequent study, Mullen et al evaluated 1509 non-cirrhotic patients undergoing hepatectomy and found older age to be an independent predictor of morbidity as well as death from liver failure.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…In addition, a slight reduction (P for trend Ͻ0.05) of the number of fenestrae was observed in the centrilobular areas of livers exposed to mildly and heavily oxLDLs. Defenestration and thickening of the sinusoidal endothelium is also associated with liver ageing in human and laboratory animals (19,28,50), and LSEC defenestration has been shown to impair the blood clearance of chylomicron remnants, leading to increased risk of cardiovascular complications (9,11,27). In the present study, we have examined the acute in vivo effects on the hepatic microcirculation of relatively high doses of oxLDL.…”
Section: Discussionmentioning
confidence: 98%